Implementation of LKPD to Improve Student Learning Outcomes - Inayati, Uun (Universitas Sebelas Maret, 2020)
The purpose of this study was to describe the application of LKPD to improve mathematics learning outcomes about time units in class III students. The type of research used is Classroom Action Research (CAR) which is carried out in three cycles, each cycle consisting of planning, implementation, observation, and reflection stages. . The subjects of this study were students of class III SD Muhammadiyah 02 Noyontaan in the 2019/2020 academic year, totaling 21 students. The method used is through the application of LKPD. Where each cycle is carried out 2 meetings. Each cycle consists of four activities, namely planning, implementing actions, observing and evaluating, and reflecting. Based on the research results, the results achieved in each cycle have increased. In the first cycle the average score was 75, and only 15 students or 75% of the students passed. In cycle II the average score is 75, students who complete 15 people or 70%. In cycle III, the average score of 84 students who completed 21 people or 100%. Based on the results obtained, it can be seen that the application of the learning model using LKPD can improve the mathematics learning outcomes of grade III students of SD Muhammadiyah 02 Noyontaan